Jing-an oral liquid alleviates Tourette syndrome via the NMDAR/MAPK/CREB pathway in vivo and in vitro - Leying Xi; Xixi Ji; Wenxiu Ji; Yue'e Yang; Yajie Zhang; Hongyan Long (Taylor & Francis Group, 2022)
Context Jing-an oral liquid (JA) is a Chinese herbal formula used in the treatment of Tourette syndrome (TS); however, its mechanism is unclear.Objective To investigate the effects of JA on amino acid neurotransmitters and microglia activation in vivo and in vitro.Materials and methods Sixty male Sprague-Dawley rats were divided into a control group and 5 TS groups. TS was induced in rats with intraperitoneal injection of 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (1 mg/kg) and in BV2 cells with lipopolysaccharide. Control and model rats were administered saline, whereas treatment groups were administered JA (5.18, 10.36, or 20.72 g/kg) or tiapride (a benzamide, 23.5 mg/kg) by gavage once daily for 21 days. Stereotypic behaviour was tested. The levels of N-methyl-d-aspartate receptor (NMDAR)/mitogen-activated protein kinase/cAMP response element-binding protein (CREB)-related proteins in striatum and BV2 cells were measured via western blots. CD11b and IBa1 levels were also measured. Ultra-high-performance liquid-chromatography was used to determine γ-aminobutyric acid (GABA), glutamic acid (Glu), and aspartic acid (ASP) levels.Results JA markedly alleviated the stereotype behaviour (25.92 ± 0.35 to 13.78 ± 0.47) in rats. It also increased NMDAR1 (0.48 ± 0.09 to 0.67 ± 0.08; 0.54 ± 0.07 to 1.19 ± 0.18) expression and down-regulated the expression of p-ERK, p-JNK, p-P38, and p-CREB in BV2 cells and rat striatum. Additionally, Glu, ASP, GABA, CD11b, and IBa1 levels were significantly decreased by JA.Discussion and conclusions JA suppressed microglia activation and regulated the levels of amino acid neurotransmitters, indicating that it could be a promising therapeutic agent for TS.